PAINTING OF THE HANDS AND FEET - V.V. Mishurovskyy (Academy of Cognitive and Natural Sciences, 2022)
In the article a role o f value o f this section of on-line tutorial is considered Wb! basic problems which arise up at drawing o f hands and feet are traced.